Double sheaths in RF discharges - Marques, L. (2005)
This paper analyzes the formation of double spacecharge sheaths, associated to the development of double ionization structures in radio frequency discharges. A simulation tool is used to generate space-time images of the ionization rate in hydrogen and in helium, obtained by inducing artificial modifications in the mobility of charged particles, with these gases